Testing Pulse Width Modulation on a TRIAC Using the Duty Cycle Approach on a Smart Conveyor - Ledyana Fitriani (Kappa Journal, 2025)
Conveyor systems have been an important element in industrial operations for extended period of time, particularly in material management. The advantage of the conveyor developed in this research lies in its energy regulation that is modified to fit the current load, in the hope of increasing the efficiency of electrical energy use. The conveyor speed control method is based on PWM (pulse width modulation), which is the setting of pulse duration to deliver current to the motor. The ATMega328 microcontroller serves as the controller in the system. When the system starts, the controller shall drive the motor based on pulse width modulation (PWM). This TRIAC perform as a phase regulator which is linked to a single-phase induction motor to operates the conveyor. The outcome show that the power generated varies depending on the load and duty cycle. With a load of 0.4 kg and a duty cycle of 20%, the power generated is 50.4 watts. Conversely, if the load increases and the duty cycle is also large, the power generated will be higher; with a load of 9.6 kg and a duty cycle of 80%, the power generated reaches 113.4 watts.